FAKTOR INTERNAL DAN EKSTERNAL YANG MEMENGARUHI KETERLIBATAN REMAJA DALAM PELAYANAN DAN KEGIATAN PERSEKUTUAN DI GEREJA KRISTEN JAWA MANAHAN - Ivenna Rindya Verdarossa; Justin Niaga Siman Juntak (STKIP Subang, 2026)
Youth participation in church ministry plays an important role in the continuity of church growth and the spiritual development of young believers. However, many churches continue to experience low levels of youth involvement in fellowship and ministry activities. This study aims to identify the internal and external factors influencing youth participation in ministry and fellowship activities at Gereja Kristen Jawa (GKJ) Manahan, Surakarta. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving pastors, youth leaders, church elders, parents, and active as well as less active youth members. The findings reveal that internal factors include personal motivation, spiritual awareness, commitment, time management, and self-confidence. External factors consist of parental support, peer influence, church programs, leadership approaches, and the overall church environment. Family support and a welcoming church community significantly encourage youth participation, while academic responsibilities, monotonous programs, and limited parental involvement often reduce participation. The study concludes that strengthening collaboration between families and church leaders, alongside developing contextual and engaging ministry programs, can effectively enhance youth involvement in church ministry